An exploratory first‐in‐man study to investigate the pharmacokinetics and safety of liposomal dexamethasone at a 2‐ and 1‐week interval in patients with metastatic castration resistant prostate cancer - Josephina P. M. Vrouwe (Wiley, 2021)
Abstract Dexamethasone has antitumor activity in metastatic castration resistant prostate cancer (mCRPC). We aimed to investigate intravenous liposome‐encapsulated dexamethasone disodium phosphate (liposomal dexamethasone) administration in mCRPC patients. In this exploratory first‐in‐man study, patients in part A received a starting dose of 10 mg followed by five doses of 20 mg liposomal dexamethasone at 2‐week intervals. Upon review of part A safety, patients in part B received 10 weekly doses of 18.5 mg. Primary outcomes were safety and pharmacokinetic profile, secondary outcome was antitumor efficacy. Nine mCRPC patients (5 part A, 4 part B) were enrolled. All patients experienced grade 1–2 toxicity, one (part B) patient experienced grade 3 toxicity (permanent bladder catheter‐related urosepsis). No infusion‐related adverse events occurred. One patient had upsloping glucose levels ≤9.1 mmol/L. Trough plasma concentrations of liposomal‐ and free dexamethasone were below the lower limit of quantification (LLOQ) in part A, and above LLOQ in three patients in part B (t1/2 ~50 h for liposomal dexamethasone), trough concentrations of liposomal‐ and free dexamethasone increased toward the end of the study. In seven of nine patients (78%) patients, stable disease was observed in bone and/or CT scans at follow‐up, and in one (part B) of these seven patients a >50% PSA biochemical response was observed. Bi‐ and once weekly administrations of IV liposomal dexamethasone were well‐tolerated. Weekly dosing enabled trough concentrations of liposomal‐ and free dexamethasone >LLOQ. The data presented support further clinical investigation in well‐powered studies. Clinical trial registration: ISRCTN 10011715.